Chronic pain and pattern of health care utilization among Malaysian elderly population: National health and morbidity survey III (NHMS III, 2006) - Zaki, L.R.M.; Hairi, N.N. (Elsevier, 2014)
Objective: The aims of this study were to report prevalence of chronic pain and to examine whether chronic pain influence healthcare usage among elderly Malaysian population. Methods: This was a sub-population analysis of the elderly sample in the Malaysia's Third National Health and Morbidity Survey (NHMS III) 2006, a nation-wide population based survey. A subset of 4954 elderly aged 60 years and above was used in the analysis. Chronic pain, pain's interference and outcome variables of healthcare utilization (hospital admission and ambulatory care service) were all measured and determined by self-report. Results: Prevalence of chronic pain among elderly Malaysian was 15.2% (95% CI: 14.5, 16.8). Prevalence of chronic pain increased with advancing age, and the highest prevalence was seen among the old-old group category (21.5%). Across young-old and old-old groups, chronic pain was more prevalent among females, Indian ethnicity, widows/widowers, rural residency and those with no educational background. Our study showed that chronic pain alone increased hospitalization but not visits to ambulatory facilities. Presence of chronic pain was significantly associated with the frequency of hospitalization (aIRR 1.11; 95% CI 1.02, 1.38) but not ambulatory care service. Conclusions: Chronic pain is a prevalent health problem among the elderly in Malaysia and is associated with higher hospitalization rate among the elderly population. This study provides insight into the distribution of chronic pain among the elderly and its relationship with the patterns of healthcare utilization. (C) 2014 Elsevier Ireland Ltd. All rights reserved.